Edukasi Pra-Nikah untuk Mencegah Berat Badan Lahir Rendah (BBLR) - Agusta Dian Ellina; Whaisna Switaningtyas; Susmini Susmini (Jurnal Abdimas Kesehatan (JAK), 2026)
Low Birth Weight (LBW) is an important indicator of infant health and remains a major public health problem, particularly in developing countries. Infants with LBW are at higher risk of neonatal complications, growth and developmental delays, infections, and non-communicable diseases later in life. Therefore, LBW reflects not only maternal and child health conditions but also preconception health readiness. Prevention efforts should not be limited to pregnancy but also focus on preconception factors influencing pregnancy outcomes. This community service activity aimed to improve knowledge and preconception health readiness among prospective couples. The activity was conducted at Wagir Primary Health Center, Malang Regency, Indonesia, from January 5 to 17, 2026. The target participants were prospective brides and grooms receiving pre-marital health services. Methods included health education, individual and small-group counseling based on health screening results, and interactive discussions. Educational media consisted of leaflets, posters, and simple presentation materials. Data were collected through observation, discussion feedback, and counseling interactions, then analyzed descriptively. The results showed an increase in participants’ understanding of preconception risk factors associated with LBW, including anemia, chronic energy deficiency, obesity, and diabetes mellitus. Participants also demonstrated improved awareness of the importance of maintaining nutritional status and health before pregnancy. Pre-marital education based on individual health risk screening is effective in improving knowledge and preconception readiness among prospective couples and has the potential as a preventive strategy to reduce LBW incidence in primary health care settings.